Socio-economic determinants of the adoption of cashew grafted plants in Benin - HINNOU, Léonard Cossi; AYEDOUN, Alfred Oluwatogni Akpado; BONOU-ZIN, Régina Dossi Clarisse; OBOSSOU, Esdras Abréwa Rêmilokoun (International Journal of Sustainable Agricultural Research, 2025)
In Benin, cashew nuts represent a socio-economic and strategic interest for farmers and the government. Cashew grafted plants have been introduced to improve productive performance. Therefore, it is essential to better assess the current adoption level of cashew grafted plants and the drivers behind it, in order to stimulate their large-scale adoption in Benin. To achieve this objective, a stratified random sample was used to select a total of 395 cashew farmers across 23 municipalities in Benin. Based on the neoclassical theory of profit maximisation, the counterfactual Average Treatment Effect (ATE) estimation framework has been used to assess the adoption rate of cashew grafted plants as well as the drivers behind their knowledge and adoption. The findings revealed a very low adoption rate of cashew grafted plants among farmers. Farmers’ perception of cashew grafted plants, level of satisfaction with the characteristics of cashew grafted plants, extension contact, household income, and household assets were the main factors determining the adoption of cashew grafted plants in Benin. Adoption constraints due to hydraulic stresses, shocks from climatic disturbances, and technical production also limited the adoption of cashew grafted plants. The study further recommends policy measures to facilitate the accessibility and availability of cashew seedlings to increase adoption and production. The government should also subsidise cashew seedlings to encourage young farmers and women, and to avoid price volatility.